Human Resources Management Flexibility as a Driver of Job Satisfaction - Haider Kasad Salal (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Contemporary educational institutions operate in rapidly changing environments that demand adaptable human resource systems. Specific Background: Although flexibility in human resource management is increasingly recognized as a foundation for strengthened organizational performance, its role in shaping job satisfaction within university settings remains insufficiently examined. Knowledge Gap: Prior studies have not fully clarified how different dimensions of HR flexibility—practices, skills, behavior, and psychological resilience—collectively contribute to employee satisfaction in higher-education institutions. Aims: This study analyzes the extent to which flexible HRM practices at the University of Kufa influence job satisfaction across various academic and administrative units. Results: Structural equation modeling shows a significant positive relationship between overall HR flexibility and job satisfaction (β = 0.75, p < 0.001), with notable contributions from skill flexibility, behavioral flexibility, psychological resilience, and flexible administrative practices. Novelty: The study offers an integrated empirical model that connects multidimensional HR flexibility with job satisfaction in a Middle Eastern higher-education context, supported by a comprehensive measurement approach adapted to the Iraqi environment. Implications: Findings highlight the necessity of adopting dynamic HR systems, expanding flexible work arrangements, and strengthening employee development mechanisms to enhance satisfaction and sustain institutional effectiveness.HIghlight : Flexible HR practices are shown to strengthen job satisfaction among employees in educational institutions. Skill and behavioral flexibility provide employees with broader capabilities that enhance their sense of value and contribution. Adaptable work arrangements support employee well-being and reinforce commitment to organizational goals. Keywords : Flexibility of Human Resources Management, Job Satisfaction, Skill Flexibility, Behavioral Flexibility, University of Kufa